Sex and the Second-Best City - Moore, Kenneth Royce (Studies in Classics, 2005)
Sex and the Second-Best City deals with the topics of sex and society in the Laws of Plato with recourse to historical context and modern critical theory. It examines reconstructions of ancient "sexuality" with a view to increased clarification. The text of the Laws is considered, along with many of its literary qualities, its influences and the utopian plan that it proposes.